Quinazoline compounds for antitumor treatment - Solyanik, G.I. (PH Akademperiodyka, 2023)
Summary. Quinazolines are among the most useful heterocyclic compounds due to their diverse chemical reactivity and a wide range of biological activity. Despite a large number of publications devoted to quinazolines and their derivatives, information is presented predominantly regarding the features of the synthesis of these compounds and their structure. The studies of specific pharmacological activity and antitumor activity of these compounds are mainly limited to primary screening using enzyme systems and cell lines. In this mini review information concerning the potential targets for antitumor action of quinazoline compounds is summarized and discussed.